Targeting TNF-α for COVID-19: Recent Advanced and Controversies - Guo, Yi; Hu, Ke; Li, Yuxuan; Lu, Chanjun; Ling, Ken; Cai, Chuanqi; Wang, Weici; Ye, Dawei (Frontiers in Public Health, 2022)
Recent advances in the pathophysiologic understanding of coronavirus disease 2019 (COVID-19) suggests that cytokine release syndrome (CRS) has an association with the severity of disease, which is characterized by increased tumor necrosis factor α (TNF-α), interleukin (IL)-6, IL-2, IL-7, and IL-10. Hence, managing CRS has been recommended for rescuing severe COVID-19 patients. TNF-α, one of the pro-inflammatory cytokines commonly upregulated in acute lung injury, triggers CRS and facilitates SARS-CoV-2 interaction with angiotensin-converting enzyme 2 (ACE2). TNF-α inhibitors, therefore, may serve as an effective therapeutic strategy for attenuating disease progression in severe SARS-CoV-2 infection. Below, we review the possibilities and challenges of targeting the TNF-α pathway in COVID-19 treatment.